Octreotide in the Management of Recurrent Gastrointestinal Bleed in Patients Supported by Continuous Flow Left Ventricular Assist Devices. Issue 1 (January 2015) - Loyaga-Rendon, Renzo Y.; Hashim, Taimoor; Tallaj, Jose A.; Acharya, Deepak; Holman, William; Kirklin, James; Pamboukian, Salpy V.
<x xml:space="preserve">Abstract</x> Gastrointestinal (GI) bleeding is the most common cause of readmission in patients supported by continuous flow left ventricular assist devices (CF-LVAD). We describe our experience in the off-label use of octreotide in the management of recurrent GI bleed in this population. Of 116 patients implanted with a CF-LVAD at our institution, seven had recurrent GI bleeding unresponsive to conventional management and were started in chronic octreotide injections. Hospitalizations due to GI bleeding, number of packed red blood cells transfused, and number of endoscopic procedures were compared 3 months before and after octreotide treatment. In the overall cohort, there were no differences in these three endpoints. When one patient with differing characteristics was excluded from the analysis there was a trend (p = 0.06) to a reduction of hospitalizations due to GI bleeding, number of blood transfusions, and number of endoscopic procedures. Octreotide exhibit a favorable trend in the frequency of admissions, blood transfusions, and endoscopic procedures in most patients with recurrent GI bleed. Further prospective studies are needed to clarify its benefits in this population.